2013
DOI: 10.1371/journal.pone.0055785
|View full text |Cite
|
Sign up to set email alerts
|

MICU2, a Paralog of MICU1, Resides within the Mitochondrial Uniporter Complex to Regulate Calcium Handling

Abstract: Mitochondrial calcium uptake is present in nearly all vertebrate tissues and is believed to be critical in shaping calcium signaling, regulating ATP synthesis and controlling cell death. Calcium uptake occurs through a channel called the uniporter that resides in the inner mitochondrial membrane. Recently, we used comparative genomics to identify MICU1 and MCU as the key regulatory and putative pore-forming subunits of this channel, respectively. Using bioinformatics, we now report that the human genome encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
453
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(482 citation statements)
references
References 32 publications
20
453
0
9
Order By: Relevance
“…This indicates that, although diversification can occur, one MICU locus is sufficient and Arabidopsis represents this minimal configuration. Furthermore, homologs of the MICU1 isoforms MICU2 and 3 that are present in vertebrates (Plovanich et al, 2013; could not be found in Arabidopsis. The amino acid sequence of Arabidopsis MICU (At-MICU; AT4G32060; predicted splicing variant 1: At-MICU.1) showed 45% similarity and 25% identity to its homolog in human.…”
Section: Micu Is Conserved In Plants With a Single Homolog In Arabidomentioning
confidence: 98%
See 2 more Smart Citations
“…This indicates that, although diversification can occur, one MICU locus is sufficient and Arabidopsis represents this minimal configuration. Furthermore, homologs of the MICU1 isoforms MICU2 and 3 that are present in vertebrates (Plovanich et al, 2013; could not be found in Arabidopsis. The amino acid sequence of Arabidopsis MICU (At-MICU; AT4G32060; predicted splicing variant 1: At-MICU.1) showed 45% similarity and 25% identity to its homolog in human.…”
Section: Micu Is Conserved In Plants With a Single Homolog In Arabidomentioning
confidence: 98%
“…Use of closely related models, including mouse and a variety of different human and other mammalian cell lines, can hamper a clear distinction of fundamental, conserved players and mechanisms from variation within the mammalian class, species, or even cell lines. For instance, three MICU isoforms of distinct function operate in mammalian cells, necessitating a complex working model of MCU regulation (Plovanich et al, 2013). Yet, the number of MICU homologs varies in eukaryotes, pointing to a specific situation in mammals that cannot be straightforwardly generalized to other Figure 8A for more images) to illustrate the overrepresentation of mitochondria with translucent matrices in the micu lines.…”
Section: Arabidopsis As a Model For Functional Analysis Of Micu And Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the single-pass transmembrane (TM) protein EMRE (Essential MCU REgulator) is absolutely required for the MCU to conduct ions (8). Two soluble components in the intermembrane space, MICU1 and MICU2, are Ca 2+ -sensing proteins that gate the activity of MCU based on outside Ca 2+ concentrations through EMRE (9)(10)(11)(12). The current consensus is that the minimum requirements for uniporter-mediated Ca 2+ flux in metazoans are MCU and EMRE, whereas in lower organisms such as Dictyostelium that lack EMRE, MCU is able to operate (13).…”
mentioning
confidence: 99%
“…The most important contributor to Mito Ca 2+ uptake is the mitochondrial calcium uniporter complex (MCUC) with the MCU serving as a highly selective channel that moves Ca 2+ ions across the IMM dependent on Mito membrane potential (ΔΨm). Recently, integrative genomics methods enabled the discovery of the molecular nature of MCU, and its regulatory subunits, MCUb, MICU1 and 2, and EMRE [22][23][24][25][26][27]. MCU is an integral membrane protein with two transmembrane domains that forms the pore through which Mito Ca 2+ currents are conducted across the IMM [22,23].…”
Section: Mito Ca 2+ Handling [Ca 2+ ] M and Mito Energetic Functionmentioning
confidence: 99%